Religious fundamentalism, right‐wing authoritarianism, and meaning in life. Issue 2 (10th November 2021) - Womick, Jake; Woody, Brendon; King, Laura A.
Abstract: Objective: Two studies examined the relationship between right‐wing authoritarianism (RWA) and religious fundamentalism (RF), and tested their unique contributions to meaning in life (MIL). Method: We recruited Amazon Mechanical Turk Participants located in the United States. Studies 1 ( N  = 827) included measures of RWA, RF, and global MIL. Study 2 ( N  = 809) additionally included measures of the facets of global MIL (existential significance, purpose, and coherence), and intrinsic religiosity. Results: In both studies, RWA, RF, and MIL were positively correlated. Partial correlations and structural equation modeling showed that, when modeled together, RF significantly contributes to MIL and RWA facets were either unrelated or negatively related. Study 2 extended these results to show that RF primarily contributed positively to global MIL through existential significance, rather than purpose or coherence. When modeled jointly with intrinsic religiosity, religious fundamentalism no longer contributed to MIL. Conclusions: These studies demonstrate that RF positively contributes to the experience of MIL, and that the link between RWA and MIL arises from their mutual overlap with RF. The link between RF and MIL is about religiosity, rather than fundamentalism. Implications are discussed.